A genre-based study of unlabelled advertorials and advertisements on products related to cardiovascular diseases / Chow Ung T’chiang - Chow , Ung T’chiang (2017)
The World Health Organization (WHO) is concerned about improper pharmaceutical advertising. Although health information is considered a fundamental part of healthcare, the WHO has called for a clear distinction between information and advertising disguised as “information”. This study investigates the promotion of over-the-counter (OTC) pharmaceutical products. It uncovers the strategies used by advertisers to bend pharmaceutical advertising regulations in order to achieve commercial interests. This study focuses on unlabelled advertorials which are accompanied by advertisements on products related to cardiovascular diseases. There are many genre analysis studies on a particular genre such as promotional genres or research genres. However, genre analyses on mixed genres and genre set in context are less established. The present research is based on the English for Specific Purposes (ESP) School of genre analysis approach and the findings expose the exploitation of rhetorical strategies through analyses on appropriation of generic resources, interdiscursivity, generic integrity and private intentions. While the study could be used as a guide for a critical genre analysis on complex genres in context, the findings could be used to address WHO’s (2007) concerns “to enact, new, or enforce existing, legislation to ban inaccurate, misleading or unethical promotion of medicines, to monitor promotion of medicines, and to develop and implement programmes that will provide independent, non-promotional information about medicines”.